2016
DOI: 10.1155/2016/6701828
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbability Enhancement of Macroporous Resin by Dielectric Barrier Discharge Plasma Treatment to Phenol in Water

Abstract: In order to enhance the adsorption efficiency and economize the use of macroporous resin, we have treated it with the dielectric barrier discharge (DBD) plasma to improve its adsorbing capacity for phenol. The effects of operation conditions, for instance, applied voltage, treated time, and air flow rate on resin, were investigated by adsorption kinetics and isotherms. Results showed that the adsorption data were in good agreement with the pseudo-second-order and Freundlich equation. Experimental results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Phenol was used to study the effect of discharge conditions in the electric field on the amount of degradation. The results of Tang et al [56] and Zhang et al [23] showed higher removal of phenol at rising voltage level due to the correlation of the input energy accelerating free electrons and the number of active species produced. Also secondary physical effects such as ultraviolet light (UV) emission and shock waves might be stronger during the discharge process at higher applied voltages, further enhancing radical formation [23].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Phenol was used to study the effect of discharge conditions in the electric field on the amount of degradation. The results of Tang et al [56] and Zhang et al [23] showed higher removal of phenol at rising voltage level due to the correlation of the input energy accelerating free electrons and the number of active species produced. Also secondary physical effects such as ultraviolet light (UV) emission and shock waves might be stronger during the discharge process at higher applied voltages, further enhancing radical formation [23].…”
Section: Introductionmentioning
confidence: 95%
“…The AOP study by Pi et al [51] indicated that the degradation of para-Chlorobenzoic acid via free radical chain reactions indirectly promotes the O 3 decomposition via intermediately formed H 2 O 2 and its subsequent reactions. Many studies of AOP systems used phenol as an indicator substance [11,23,[52][53][54][55][56][57][58]. This aromatic substance can be degraded by both radical mechanisms and direct reaction with O 3 [54,55].…”
Section: Introductionmentioning
confidence: 99%